The Role of Self-Efficacy and Competence in International Student’s Sociocultural Adaptation - Rakhman Ardi; Mutia Az Zahra (Indigenous: Jurnal Ilmiah Psikologi, 2024)
This study examines the role of self-efficacy in intercultural communication as a mediator between competence perception and sociocultural adaptation among international students in Japan. The research uses a quantitative approach with convenience sampling technique, and obtains 92 international student participants. Several validated questionnaires are utilized, namely the Sociocultural Adaptation Scale (SCAS), a = 0.874 by Ward & Kennedy (1999) adapted by Simic-Yamashita & Tanaka (2010); Self-Efficacy in Intercultural Communication (SEIC) a = 0.914 by Peterson et al., (2011); Japanese Proficiency by Iwao & Hagiwara (1988); and Intercultural Communication Competence (ICC), a = 0.691 adapted by Gonçalves et al. (2020) from Arasaratnam (2009). A hypothesis model is constructed with competence perception as the predictor, self-efficacy as the mediator, and sociocultural adaptation as the dependent variable. Competence perception is a latent variable measured by two manifest variables: intercultural communication competence and Japanese language proficiency. Data analysis is conducted using Path Analysis, a form of Structural Equation Modeling (SEM), with results indicating that the hypothesis model has an acceptable fit index. Although the proposed hypothesis model as a whole can be confirmed, a significant effect is found in the direct path between competence perception and sociocultural adaptation, while the indirect path is not significant. This means that self-efficacy does not act as a mediator, but rather as a predictor in sociocultural adaptation. The practical implications of this study emphasize the importance of stakeholders, such as international offices at universities, paying attention to the role of language proficiency, intercultural communication competence, and self-efficacy in international migrant students, especially in taking preventive or curative actions for adaptation problems.